Analisa Laporan Keuangan Syariah dalam Metode Akuntansi Akrual Basis (Studi Kasus pada PT BPRS Jabal Tsur Pandaan): Sharia Financial Statement Analysis in Accrual Basis Accounting Method (A Case Study at PT BPRS Jabal Tsur Pandaan) - Mariyah Ulfah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2018)
The rapid growth of Islamic banking in East Java necessitates rigorous health assessments to ensure stability and compliance with sharia principles. This study addresses the critical issue of applying accrual-based accounting in sharia financial reporting, particularly for profit-sharing contracts. The research aims to evaluate the financial health of PT BPRS Jabal Tsur Pandaan using the CAMEL method (Capital, Assets, Management, Earnings, Liquidity). A quantitative descriptive approach was employed, involving document analysis, interviews, and questionnaires. Data were analyzed using CAMEL ratios as prescribed by Bank Indonesia. The findings reveal that PT BPRS Jabal Tsur Pandaan achieved a CAR of 13.91, BDR of 10.9, management score of 22.1, ROA of 0, BOPO of 36.8, and LDR of 2.8, resulting in a total CAMEL score of 86.51. It is concluded that the bank is classified as